Functional analysis of the acetylation of human p53 in DNA damage responses - Chung, Sun-Ku (Higher Education Press, 2014)
As a critical tumor suppressor, p53 is inactivated in human cancer cells by somatic gene mutation or disruption of pathways required for its activation. Therefore, it is critical to elucidate the mechanism underlying p53 activation after genotoxic and cellular stresses. Accumulating evidence has indicated the importance of posttranslational modifications such as acetylation in regulating p53 stability and activity. However, the physiological roles of the eight identified acetylation events in regulating p53 responses remain to be fully understood. By employing homologous recombination, we introduced various combinations of missense mutations (lysine to arginine) into eight acetylation sites of the endogenous p53 gene in human embryonic stem cells (hESCs). By determining the p53 responses to DNA damage in the p53 knock-in mutant hESCs and their derivatives, we demonstrate physiological importance of the acetylation events within the core domain (K120 and K164) and at the C-terminus (K370/372/373/381/382/386) in regulating human p53 responses to DNA damage.